Additive manufacturing of polymers and composites for sustainable engineering applications - C, Pradeep Raja; S, Vigneshwaren; Parrthipan, B. K.; Babu, S.; Kathik Babu, N. B.; Mensah, Rhoda Afriyie (Frontiers in Chemical Engineering, 2025)
Additive manufacturing has rapidly emerged as a transformative and inherently sustainable technology in engineering. It enables the fabrication of components with minimal or near-zero material wastage. While additive manufacturing was initially focused on metals, it now includes polymers, ceramics, composites, and biomaterials, providing an efficient platform to produce sustainable materials. This review provides a comprehensive overview of additive manufacturing techniques for non-metal materials and emphasises their potential to minimise waste, promote resource circularity, and support sustainable production. Particular attention is given to polymer-based techniques such as fused deposition modelling, stereolithography, and selective laser sintering. These techniques offer design flexibility, reduced material wastage, and compatibility with recycled and bio-based feedstocks. This review highlights the major advantages and practical applications of polymer-based materials in biomedical engineering, microelectronics, flame-retardant and conductive systems, and multifunctional composites. While most limitations are presently observed in flame-retardant systems, a comparative discussion is also provided for the other application domains to maintain balance across the sections. Additionally, emerging research on sustainable and bio-derived polymers such as PLA and PHB reinforced with carbonised biomass or eco-friendly conductive fillers is introduced to emphasise environmentally responsible pathways for developing next-generation conductive materials. Overall, this review highlights additive manufacturing as a sustainable pathway for material valorisation and innovation within waste-to-material and waste-to-energy frameworks.